Dissecting genetic loci of yield, yield components, and protein content in bread wheat nested association mapping population - Donaire, Guillermo Manuel (2023)
In the last century wheat breeding programs have shown consistent yield increases, often associated with lower grain protein concentrations (GPC). A better understanding of the genetic basis of grain yield and grain protein content can help break the grain yield—GPC negative correlation. We developed a nested association mapping population composing a set of spring wheat genotypes for genetic dissection of grain yield and quality with ‘Blanca Fuerte’ (high yield and low grain protein content) as recurrent parent and cultivars and advanced lines from CIMMYT and California (UC Davis breeding program, medium–high yield and grain protein content). The QTL analyses revealed three genomic regions on chromosomes 2B, 6A, and 6B associated with significant increases in GPC but negative effects on yield, and one region on chromosome 5B associated with significant increases in grain yield but negative effects on GPC. More interestingly, we identified two genomic regions on chromosomes 2B and 3B associated with increases in GPC and no significant effects on grain yield and a genomic region on chromosome 1A associated with a significant increase in grain yield and no penalty in GPC. These last three genomic regions and their associated markers are promising tools for wheat breeding programs interested in breaking the negative correlation between GPC and grain yield.